Does Economic Freedom Foster Tolerance? - Niclas Berggren; Therese Nilsson (Lund University, School of Economics and Management, Department of Economics, 2012)
Tolerance has the potential to affect both economic growth and wellbeing. It is therefore important to discern its determinants. We add to the literature by investigating whether the degree to which economic institutions and policies are market-oriented is related to different measures of tolerance. Regression analysis of up to 65 countries reveals that economic freedom is positively related to tolerance towards homosexuals, especially in the longer run, while tolerance towards people of a different race and a willingness to teach kids tolerance are not strongly affected by how free markets are. Stable monetary policy and outcomes is the area of economic freedom most consistently associated with greater tolerance, but the quality of the legal system seems to matter as well. We furthermore find indications of a causal relationship and of social trust playing a role as a mechanism in the relationship between economic freedom and tolerance and as an important catalyst: the more trust in society, the more positive the effect of economic freedom on tolerance.
Keywords: P10; P48; Z13; 330; Markets; Economic freedom; Tolerance; Government; Institutions; Regulation